RNA-ligant interactions. (I) Magnesium binding sites in yeast tRNAPhe. - Holbrook, S R (1977)
X-ray crystallagraphic studies studies indicate that there are at least four site-specifically bound hydrated Mg2+ ions, [Mg(H2O)n]2+, in yeast tRNAPhe. The size and the octahedral coordination geometry, rather than the charge, of [Mg(H2O)N]2+ appear to be the primary reasons for the specificity of magnesium ions in site-binding and in the stabilization of the tertiary structure of tRNA.